2014
DOI: 10.1111/and.12310
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation assessment: morphometric study of human spermatogonial stem cells in recipient mouse testes

Abstract: The purpose of this study was (i) To establish in vitro propagation of human spermatogonial stem cells (hSSCs) from small testicular biopsies to obtain a high number of cells; (ii) to evaluate the presence of functional hSSCs in culture system by RT-PCR using DAZL, α6-Integrin, β1-Integrin genes; and (iii) to evaluate the effects of cell concentration on successful xenotransplantation of hSSCs in mice testis. Donor hSSCs were obtained from men with maturation arrest of spermatogenesis duration 1 year ago. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Disruption of the Dmc1 gene leads to fail in homologous chromosome synapsis formation and causes meiotic cell death. It was speculated that the absence of this meiotic gene may be an indication for differentiation arrest of spermatogonia cells at the premeiotic stages in the culture system in this study (Mirzapour, Movahedin, Koruji, & Nowroozi, ). Therefore, in our study, spermatocytes and spermatids were not observed at the light and electron microscopic level.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Disruption of the Dmc1 gene leads to fail in homologous chromosome synapsis formation and causes meiotic cell death. It was speculated that the absence of this meiotic gene may be an indication for differentiation arrest of spermatogonia cells at the premeiotic stages in the culture system in this study (Mirzapour, Movahedin, Koruji, & Nowroozi, ). Therefore, in our study, spermatocytes and spermatids were not observed at the light and electron microscopic level.…”
Section: Discussionmentioning
confidence: 79%
“…In this situation where there is an accumulation of spermatogonia, probably apoptosis of damaged spermatogonia does eventually occur because of failure of the density regulatory system. The expression of Bax gene was observed approximately 32–35 days after culture (the results were not shown; Mirzapour et al., ). Therefore, ever time, some changes take place, which could cause a delay in cell growth and proliferation of SSC colonies.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, several teams attempted to find a culture system of dissociated testicular cell suspensions (TCSs) able to propagate human SSCs in vitro (Table 1). [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Sadri-Ardekani et al adapted the protocol developed by Kanatsu-Shinohara et al for human testicular cells (TCs). Briefly, this culture system relies on the capacity of somatic cells to adhere to the plate while the germ-cell fraction stays in suspension, allowing enrichment of SSCs after differential plating.…”
Section: Ssc Propagationmentioning
confidence: 99%
“…32,33 This technique led to an 18,450-fold enrichment of adult SSCs after 64 days and to a 9.6-fold enrichment of prepubertal SSCs after 11 days of culture using xenotransplantation as the gold standard to identify SSCs able to migrate along the basement membrane of the STs, colonize their niches, and generate germ-cell colonies. Among researchers who have xenotransplanted long-term cultured human SSCs, 32,33,39,40,42,43,51 only Sadri-Ardekani et al and Nickkholgh et al quantified SSCs in STs after transplantation and demonstrated SSC enrichment. 32,33,43 However, several other teams using the same protocol could not reproduce such results due to the complexity and skills needed to distinguish between SSCs and human embryonic stem cell-like (hESC-like) cells, 34 because of low germ-cell survival and overgrowth of remaining somatic cells.…”
Section: Ssc Propagationmentioning
confidence: 99%
“…Traditionally, this has been approached through experimental designs involving live animals. The development of techniques such as specific molecular probes and xenografting of testicular tissues opened a new era of study on factors affecting spermatogenesis (811). …”
Section: Reproductive Physiology and Pathology In The Malementioning
confidence: 99%